STUDI PENDAHULUAN ENZIM KITINASE EXTRASELULER YANG DIHASILKAN OLEH ISOLAT BAKTERI ASAL MANADO 1) [Preliminary Study of Extracellular Chitinase Produced by Bacteria Isolated from Manado] - E. Y. Purwani; A. Toharisman; E. Chasanah; J. F. Laksmi; V. Welan; M. T. Suhartono; T. Purwadaria; J. K. Hwang; Y. R. Pyun (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2002)
Chitinolytic bacteria were isolated from several exotic area in Manado Province. The most potential isolate, namely 13.26, was isolated from Tompaso. The isolate was cultured in the thermus medium containing colloidal chitin as a carbon source for 5 days at 55°C to produce chitinase. It was observed that chitinase was most active at 65°C and the optimum pH was 8 in boric acid-borax buffer. Ammonium sulfate (50% saturation) precipitation of the protein increased the specific activity of the enzyme from 0.20 unit/mg protein (in culture supernatant) to 0.28 unit/mg protein. The molecular weight as estimated by zymogram analysis was180 kDa.